The Relationship between the Implementation of RET Counseling with Motivation Complete Thesis College Student - Muhammad Junaedi Mahyuddin; Handayani Sura; M. Yasdar; Lisa Lisa; Rismajayanti Rismajayanti; Nurul Aifah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Problem study is how connection Among implementation RET with motivation complete the student's final project at the University of Muhammadiyah Enrekang, Faculty of Teacher Training and Education Education. Destination The purpose of this research is to find out whether there is a relationship between the implementation of RET with motivation complete Duty end college student University Muhammadiyah Enrekang Faculty teacher Knowledge Education.Research this classified as study descriptive quantitative . This research is all students of class 2016 – 2017 in Six Study Programs Faculty of Teacher Training Education (FKIP) totaling 150 people. A sample of 108 people was drawn using a purfosive technique random sampling. Instrument study is questionnaire, interview, and documentation. Technique analysis data used in this research is descriptive quantitative by using the distribution table frequency percentage.Result study show that part big attitude college student to implementation of RET Counseling on the motivation to complete the final project. In Study Program under the auspices of the Faculty of Science Education University Muhammadiyah Enrekang is enough good that is college student motivation final task completion. After drawing conclusions, some suggestions can be given, namely: (1) Department leaders and teaching staff, namely lecturers, should pay more attention to students by providing services in the form of services to students who have difficulty in completing their final assignments they, so that college student could understand what which want to achieved for the sake of destination together. (2) For students, must understand and think rationally that the final project is neither torture nor a scary task but a task to complete and also fun. (3) For Researchers relevant, are expected to conduct similar research but in the form of case studies or survey for see more far from the impact counseling RET the.